2012
DOI: 10.1590/s0037-86822012000300027
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinitis and pericardial effusion in a patient with AIDS and disseminated Mycobacterium avium infection: a case report

Abstract: We report the case of a 36-year-old man who had acquired immune deficiency syndrome and developed suppurative mediastinitis extending over the left lung and anterior thoracic wall around the sternum, pericardial effusions, splenomegaly, and mesenteric and periaortic lymphadenomegaly due to Mycobacterium avium (genotype I). The organism was isolated from an axillary lymph node and the bone marrow. Mediastinitis associated with disseminated M. avium complex infection is uncommon and, to the best of our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Many species of actinomycetes such as nocardia, mycobacterium, and ie, are increasingly being recognized as important human pathogens in both immunocompetent and immunocompromised patients. 17,33,34 The clinical presentation and severity of disease and the prognosis in an infected patient are extremely variable and may be determined by several factors such as the route of infection and the functioning level of the immune system. 5,35 Likewise, accurate identification and DST of actinomycetes clinical isolates is a significant decision support tool which may help clinicians in order to select more appropriate therapy and, thus, improve the management and outcomes of some important actinomycetes diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of actinomycetes such as nocardia, mycobacterium, and ie, are increasingly being recognized as important human pathogens in both immunocompetent and immunocompromised patients. 17,33,34 The clinical presentation and severity of disease and the prognosis in an infected patient are extremely variable and may be determined by several factors such as the route of infection and the functioning level of the immune system. 5,35 Likewise, accurate identification and DST of actinomycetes clinical isolates is a significant decision support tool which may help clinicians in order to select more appropriate therapy and, thus, improve the management and outcomes of some important actinomycetes diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymphadenitis caused by M. avium complex is rare, and has been reported in immunocompromised hosts [8,9]. To the best of our knowledge, the present report is the first describing axillary lymphadenitis caused by M. intracellulare in an immunocompetent host.…”
Section: Discussionmentioning
confidence: 64%
“…The condition commonly occurs in the neck, and it has been suggested that the reason for this is that NTM—which adheres to the inside of the oral cavity or pharynx—enters via the tonsillar lymph nodes and induces the development of lymphadenitis of the neck or both the head and the neck. Reports describing cases of axillary lymphadenitis caused by NTM are limited, and the cause may be related to trauma, especially tenosynovitis [13], or HIV infection [8]. There is also one report of an 8-month-old infant with axillary lymphadenitis caused by MAC [9], but notably, that infant was HIV-positive.…”
Section: Discussionmentioning
confidence: 99%
“…avium subsp. avium is pathogenic for birds but can cause opportunistic infections in AIDS patients, whereas M. avium subsp.…”
Section: Resultsmentioning
confidence: 99%